Lifestyle Habits and Health Indicators in Migrants and Native Schoolchildren in Chile - Cofre-Bolados, C; Pizarro-Quevedo, T; Suarez-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In Chile, the migrant population has increased in the last years. Migrants adopt behaviors of this new culture, which can have an effect on their health. Contradictory results regarding differences between migrant and native children have been reported. The aim of this study was to explore the associations between nationality with health indicator and lifestyle habits among schoolchildren in Chile. A cross-sectional and observational study with a non-probabilistic sample was conducted in 1033 children (86.4% Chilean and 13.6% migrant) from second to fourth grade of seven public schools from low-income municipalities from the Metropolitan Region, Chile. Anthropometric measurements (weight, height, waist circumference, triceps and subscapular folds), handgrip strength, and standing long jump measurements, physical activity, self-esteem and food guidelines accomplishments were determined. Migrant children presented lower body mass index (BMI), Z-BMI, body fat% and waist circumference values; and higher handgrip strength, standing long jump, and more satisfactory compliance with food guidelines than natives (p < 0.05). No significant difference for physical activity and self-esteem was observed. In the adjusted models, migrants presented lower odds for overweight/obesity, risk of abdominal obesity, low handgrip strength and unsatisfactory food guidelines accomplishment in all models (p < 0.05). The nutritional and muscular fitness of migrant children was better than that of the Chilean ones. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.